At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To solve the problem, we start with the given equation
[tex]\[ \sin A + \csc A = 3 \][/tex]
Recall that [tex]\(\csc A = \frac{1}{\sin A}\)[/tex]. Substituting this into the equation, we get:
[tex]\[ \sin A + \frac{1}{\sin A} = 3 \][/tex]
Let [tex]\(\sin A = x\)[/tex]. Then the equation becomes:
[tex]\[ x + \frac{1}{x} = 3 \][/tex]
Multiplying through by [tex]\(x\)[/tex], we get:
[tex]\[ x^2 + 1 = 3x \][/tex]
Rearranging the terms gives us a quadratic equation:
[tex]\[ x^2 - 3x + 1 = 0 \][/tex]
We can solve this quadratic equation using the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -3\)[/tex], and [tex]\(c = 1\)[/tex]. Substituting these values in, we get:
[tex]\[ x = \frac{3 \pm \sqrt{9 - 4}}{2} \][/tex]
[tex]\[ x = \frac{3 \pm \sqrt{5}}{2} \][/tex]
So, the solutions for [tex]\(x\)[/tex] are:
[tex]\[ x = \frac{3 + \sqrt{5}}{2} \quad \text{and} \quad x = \frac{3 - \sqrt{5}}{2} \][/tex]
These solutions correspond to:
[tex]\[ \sin A = \frac{3 + \sqrt{5}}{2} \quad \text{and} \quad \sin A = \frac{3 - \sqrt{5}}{2} \][/tex]
Next, we need to evaluate [tex]\(\frac{\sin^4 A + 1}{\sin^2 A}\)[/tex] for each value of [tex]\(x\)[/tex].
Starting with the first solution, [tex]\(\sin A = \frac{3 + \sqrt{5}}{2}\)[/tex]:
[tex]\[ \frac{\left(\frac{3 + \sqrt{5}}{2}\right)^4 + 1}{\left(\frac{3 + \sqrt{5}}{2}\right)^2} \][/tex]
For the second solution, [tex]\(\sin A = \frac{3 - \sqrt{5}}{2}\)[/tex]:
[tex]\[ \frac{\left(\frac{3 - \sqrt{5}}{2}\right)^4 + 1}{\left(\frac{3 - \sqrt{5}}{2}\right)^2} \][/tex]
After solving these for the expressions, we get:
Simplifying these terms yields the results that were previously mentioned. Thus, the final solutions are derived as follows, without showing intermediate steps for the algebraic polynomials:
[tex]\[ \frac{(\sin A)^4 + 1}{(\sin A)^2} \][/tex]
For the solutions [tex]\(\sin A = \frac{3 + \sqrt{5}}{2}\)[/tex] and [tex]\(\sin A = \frac{3 - \sqrt{5}}{2}\)[/tex], the detailed stepwise solutions will lead us to the acceptable results:
[tex]\[ 1 + \left(\frac{3 + \sqrt{5}}{2}\right)^2 \quad \text{and} \quad \left(\frac{3 - \sqrt{5}}{2}^2\right) + 1 \][/tex]
[tex]\[ \sin A + \csc A = 3 \][/tex]
Recall that [tex]\(\csc A = \frac{1}{\sin A}\)[/tex]. Substituting this into the equation, we get:
[tex]\[ \sin A + \frac{1}{\sin A} = 3 \][/tex]
Let [tex]\(\sin A = x\)[/tex]. Then the equation becomes:
[tex]\[ x + \frac{1}{x} = 3 \][/tex]
Multiplying through by [tex]\(x\)[/tex], we get:
[tex]\[ x^2 + 1 = 3x \][/tex]
Rearranging the terms gives us a quadratic equation:
[tex]\[ x^2 - 3x + 1 = 0 \][/tex]
We can solve this quadratic equation using the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -3\)[/tex], and [tex]\(c = 1\)[/tex]. Substituting these values in, we get:
[tex]\[ x = \frac{3 \pm \sqrt{9 - 4}}{2} \][/tex]
[tex]\[ x = \frac{3 \pm \sqrt{5}}{2} \][/tex]
So, the solutions for [tex]\(x\)[/tex] are:
[tex]\[ x = \frac{3 + \sqrt{5}}{2} \quad \text{and} \quad x = \frac{3 - \sqrt{5}}{2} \][/tex]
These solutions correspond to:
[tex]\[ \sin A = \frac{3 + \sqrt{5}}{2} \quad \text{and} \quad \sin A = \frac{3 - \sqrt{5}}{2} \][/tex]
Next, we need to evaluate [tex]\(\frac{\sin^4 A + 1}{\sin^2 A}\)[/tex] for each value of [tex]\(x\)[/tex].
Starting with the first solution, [tex]\(\sin A = \frac{3 + \sqrt{5}}{2}\)[/tex]:
[tex]\[ \frac{\left(\frac{3 + \sqrt{5}}{2}\right)^4 + 1}{\left(\frac{3 + \sqrt{5}}{2}\right)^2} \][/tex]
For the second solution, [tex]\(\sin A = \frac{3 - \sqrt{5}}{2}\)[/tex]:
[tex]\[ \frac{\left(\frac{3 - \sqrt{5}}{2}\right)^4 + 1}{\left(\frac{3 - \sqrt{5}}{2}\right)^2} \][/tex]
After solving these for the expressions, we get:
Simplifying these terms yields the results that were previously mentioned. Thus, the final solutions are derived as follows, without showing intermediate steps for the algebraic polynomials:
[tex]\[ \frac{(\sin A)^4 + 1}{(\sin A)^2} \][/tex]
For the solutions [tex]\(\sin A = \frac{3 + \sqrt{5}}{2}\)[/tex] and [tex]\(\sin A = \frac{3 - \sqrt{5}}{2}\)[/tex], the detailed stepwise solutions will lead us to the acceptable results:
[tex]\[ 1 + \left(\frac{3 + \sqrt{5}}{2}\right)^2 \quad \text{and} \quad \left(\frac{3 - \sqrt{5}}{2}^2\right) + 1 \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.